2004
DOI: 10.2202/1548-923x.1057
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Master's Education in Nursing

Abstract: This qualitative, descriptive study examined changes in perspective experienced by 22 recent graduates of Master's in Nursing programs from three Ontario universities. Participants responded to semi-structured, taped interviews and recounted personal, practice, and attitudinal changes they could attribute to completing a Master's program in Nursing. Among outcomes were personal ones including greater self-confidence, credibility, and acuity of critical thinking. Deeper and broader world-views of the profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
14
1
1
Order By: Relevance
“…However, the survey findings of a lack of confidence in communicating with medical staff and also lack of respect that they experienced in the workplace are contrary to the focus group findings and to the findings of other researchers who have found instead that collaboration and communication may be improved through postgraduate education [19,27,28,[42][43][44][45]. This finding is of real concern not only because patients of health professionals that work well together suffer lower mortality rates [46] but that the positive impact of such a culture on teamwork and healthcare effectiveness [10] may have been underrealised in the study setting.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the survey findings of a lack of confidence in communicating with medical staff and also lack of respect that they experienced in the workplace are contrary to the focus group findings and to the findings of other researchers who have found instead that collaboration and communication may be improved through postgraduate education [19,27,28,[42][43][44][45]. This finding is of real concern not only because patients of health professionals that work well together suffer lower mortality rates [46] but that the positive impact of such a culture on teamwork and healthcare effectiveness [10] may have been underrealised in the study setting.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, postgraduate study is expected to enhance the implementation of evidence into practice [18,19] and to increase nurses' confidence in their ability [20][21][22][23][24]. On the other hand from an intrinsic, critical perspective, nurses who have completed postgraduate education have also been found to be more likely to be critical thinkers [25] and advocates for patients by questioning treatment decisions and options [25][26][27], and to be supported to develop personally and professionally [17,28,29].…”
Section: Advances In Nursingmentioning
confidence: 99%
“…Only three articles used a mixed methods approach. Cragg and Andrusyszyn [37] mention ‘four focus groups with a total of nine participants’, which does not meet the quality criteria for focus group discussions [38]. The study designs were generally of low quality [36], ie comprising of case series and depending mostly on self-reporting, with little triangulation.…”
Section: Resultsmentioning
confidence: 99%
“…In a number of studies, graduates reported improvement in the clinical care they provided [22,42-46] and in their attitude towards patients [43,47]. Alumni also reported enhanced self-confidence [22,23,29,37,43,48,49]. …”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, they did not value advancing their education because they do not see the relevance to the changes in health care nor the contributions they could make by having a postgraduate qualification. If one accepts the evidence that having a more highly educated nursing workforce makes a difference to patient outcomes (L. H. Aiken et al, 2012;Armstrong & Adam, 2002;Bahn, 2007b;Chaboyer et al, 2001;Cooley, 2008;Cragg & Andrusyszyn, 2004;Robert Wood Johnson Foundation, 2013), then getting these NPGE nurses to advance their educational level will be paramount. To meet the growing complexities within health care in Australia, a substantial investment will be required from the government (policymakers), healthcare organisations (employers) and healthcare educators (universities) as well as from the registered nurses.…”
Section: Ismentioning
confidence: 99%